Reasonable application analysis of Casnter graphitization furnaces according to the demands of modern market - Панов, Евгений Николаевич; Педченко, Анатолий Юрьевич (Technology audit and production reserves, 2014)
Analysis of the global market has shown that the production of graphite electrodes (GE) depends on the production of steel in electric arc steel furnaces. The growth of world production is the main driver of the market development of graphite electrodes. Acheson-type graphitization of GE was extremely energy intensive and therefore costly, but was necessary to manage previously poor coke qualities with high sulfur and nitrogen content. Although invented earlier, the more economic Castner, or so called lengthwise graphitization, was not applicable until the development of electrical rectifiers for these high currents. As these became available and needle coke with low sulfur and nitrogen was invented, lengthwise graphitization became the standard in the Western World for GE production. Manufacturing requires high-quality large-diameter electrodes. They must be technically and economically advisable for the usage only in directly-fired furnaces by Castner method. But the given technology is not fully realized in Ukraine. First of all, it`s so due to the absence of significant investment in electrode industry. Although, as the analysis of modern market of electrode industry has shown, the situation is changing and new requirements are emerging now.